Surveys of vehicle colour frequency and the transfer of vehicle paints to stationary objects in Sydney, Australia. (March 2015) - Jackson, Fiona; Bunford, Joanna; Maynard, Philip; Roux, Claude
Highlights: Frequency of the colour of vehicles observed on. Frequency of vehicle paint colours transferred to car park pillars and walls. The highest frequency of vehicle colours recorded was white, grey, black and blue. The most commonly seen colours in car parks are blue, white, red, and silver. Similar results to previous vehicle surveys and vehicle colour registration data. Abstract: The interpretation of vehicle paint traces in forensic casework hinges on a number of factors including the type of paint, colour, number of layers, and background information. Vehicle colour surveys are an important source of information for the forensic paint examiner when interpreting the level of significance of a paint transfer between vehicles involved in a collision, or smears of vehicle paint left at a scene. The two surveys that are presented here investigated (i) the frequency of the colour of vehicles observed on both a motorway and suburban roads in Western Sydney and (ii) the frequency of different vehicle paint colours transferred to car park pillars and walls from five different car parks within North West Sydney, Australia. In the first survey, the highest frequency of vehicle colours recorded was white, grey, black and blue. The second survey resulted in very similar findings with the four most commonly seen colours across the five car parks being blue, white, red, and silver. The results in the second survey take into account the potential for anomalies within the data due to the use of painted service vehicles used within the car parks, such as trolleys and trailers. The results from both surveys were very similar to previous vehicle colour surveys that have been conducted and also corresponded to the vehicle colour registration data obtained from the NSW Roads and Maritime Service website. The results from these two surveys provide up to date statistics that can assist the forensic paint examiner with valuable background data when assessing the significance of vehicle paint evidence in casework.